ATTENTION TO WOMEN’S HEALTH IN INFANTS WITH SARS-COV-2: INTEGRATIVE LITERATURE REVIEW - Ferreira Brandão, Adams; Silva de Mendonça, Guilherme (Health and Society, 2023)
Objective: To analyze, through an integrative literature review, articles on nursing care for lactating women affected by Sars-CoV-2 infection. Method: Integrative literature review carried out from March/2020 to May/2021. The descriptors were used: Nursing Care, SARS-CoV-2, Women’s Health. Results: This integrative review resulted in 04 articles, all published in the year 2020. Conclusion: This work deals with a subject of how nursing care is being performed in women’s health in the postpartum period during the Sars-CoV pandemic -two. It is concluded that there have been some changes in hospital care, such as: isolation between mother and child.